2022
DOI: 10.2147/jir.s343432
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating CD4+ Central Memory T Cells Correlated with Favorable Prognosis in Oral Squamous Cell Carcinoma

Abstract: Objective Oral squamous cell carcinoma (OSCC) is the most frequent oral malignancy with a poor prognosis, in which tumor-infiltrating immune cells may play a critical role. Therefore, our study aims to screen potential immune cells and immune-related genes for predicting OSCC prognosis. Methods A total of 310 OSCC patients with full transcriptional data and clinical characteristics were extracted from the TCGA database. Then, we obtained their abundance of tumor-infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Central memory CD8 + T cells have been shown to exert strong antitumor activity and have been associated with a better prognosis in cancer patients ( 32 ). Central memory CD4 + T cells have also been proposed as an independent prognostic biomarker of oral squamous cell carcinoma ( 33 ). Natural killer cells not only exert antitumor effects via direct cytolytic activity but also indirectly exert antitumor effects through cytokine production ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Central memory CD8 + T cells have been shown to exert strong antitumor activity and have been associated with a better prognosis in cancer patients ( 32 ). Central memory CD4 + T cells have also been proposed as an independent prognostic biomarker of oral squamous cell carcinoma ( 33 ). Natural killer cells not only exert antitumor effects via direct cytolytic activity but also indirectly exert antitumor effects through cytokine production ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…43 The complex cross-talk between cancer cells and immune cells plays an important role in the tumor development and progress. 44 Wu and colleagues 45 recently performed Cox regressions to identify the immune cells associated with OSCC survival. The results revealed that CD4 + central memory T as an independent immune cell was significantly associated with the prognosis of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that a low central memory CD4 T cell expression level was associated with longer PFS in the sintilimab arm. The function of central memory CD4 T cells in the tumor microenvironment remains unclear [ 41 , 42 ]. However, it was reported that transforming growth factor‐β could induce CD4+CD62L+ central memory T cells to differentiate into Foxp3+ T cells [ 43 ], which might then suppress immune reaction and lead to worse survival.…”
Section: Discussionmentioning
confidence: 99%